Korelasi Antara Transparansi Lembaga Pengelola Zakat dengan Tingkat Kepercayaan Muzakki dalam Membayar Zakat di Badan Amil Zakat Nasional (BAZNAS) Kota Palembang - Erdah Litriani; Disfa Lidian Handayani; Citra Lestari (Jurnal I-Philanthropy, 2021)
This study discusses the correlation between the transparency of zakat management institutions and the level of trust of muzakki in paying zakat at the National Amil Zakat Agency (BAZNAS) Palembang City. With the formulation of the problem, how is the correlation between the transparency of zakat management institutions and the level of trust of muzakki in paying zakat at the National Amil Zakat Agency (BAZNAS) in Palembang. Which aims to determine the correlation between the transparency of zakat management institutions with the level of trust of muzakki in paying zakat at the National Amil Zakat Agency (BAZNAS) Palembang city and donations to related institutions for policy formulation in zakat management. This research uses quantitative research. Quantitative research methods can be interpreted as research methods based on causal relationship symptoms, used for population research and certain samples, data collection using research instruments, quantitative data analysis, with the aim of testing predetermined hypotheses. From the results of the product moment correlation analysis, the figure is 71.18%. This value is getting closer to 1. Thus, it can be concluded that there is a close relationship between institutional transparency and muzzaki trust in the management of zakat funds at Baznas. The better the transparency of Baznas, the more muzzaki's trust in the Baznas institution in the management (collection and distribution) of zakat funds will be.